Cultural Adaptation of Sedulur Sikep: Community-Based Disaster Risk Reduction Strategy in Baturejo Village - Arumdati, Dominika Oktavira (International Journal Labs, 2023)
Background: Integration of various knowledge in response to various things that interfere with their existence both geographically, economically, socially maintaining livelihood assets, encouraging changes in the context of life of the Sedulur Sikep community. The perspective of political ecology in the context of disasters due to development impacts is responded by collaboration built as a network with academics, non-governmental organizations, legal aid institutions and the media. Aim: This study generally aims to analyze the cultural adaptation carried out by the Sedulur Sikep community in Baturejo Village. Method: This study combines habitus theory and cultural adaptation with the Sustainable Livelihood Framework approach to understand aspects and characteristics of Sedulur Sikep life in rural Baturejo. Community-based disaster risk reduction carried out by Sedulur Sikep was investigated qualitatively using the Participatory Rural Appraisal method to see with various variables, namely: potential and access to resources, vulnerability and capacity, processes and involvement in the Kendeng Care Community network, and see the extent of global/market influence on Sedulur Sikep's vulnerability. Data was obtained through interviews and observations. Inductive writing method that is done descriptively. Findings: The management of knowledge contained in social values in Sedulur Sikep to maintain the balance of living order with nature is the response capacity of Sedulur Sikep in maintaining livelihood assets and mainstreaming community-based disaster risk reduction in the nature of prevention and mitigation.